A perspectiva do deficiente intelectual adulto sobre o envelhecimento - Girardi, Mirtha (2013)
The world's population, and especially the Brazilian population, is aging and the increase in life expectancy is due to the modifications that are occurring in attendance, in the help and in the development of new medical practices and in cultural changes that bring better conditions and quality of life for those who ages. Considering that they are part of the population who are aging, the intellectually disabled also experience such changes. This study aimed at knowing how the adult intellectual disabled perceives aging and what are their expectations toward their own aging. The study used a qualitative approach of an exploratory and descriptive and used the sensitive creative method for collection and analysis of data. The sample consisted of ten intellectually disabled adults, who frequented the APAE in Passo Fundo - RS. Data collection occurred in the second semester of 2012 with three workshops of creativity and sensitivity. The results were compiled in a scientific production which is attached in this text entitled "Old are others":perceptions of aging of adults with intellectual disabilities , which initially showed that aging of the intellectually disabled is coinciding with the aging of their parents or caregivers, as well as showed that the research participants understand that there is passage of time, however, they do not relate this passage to their own aging. Thus, the research participants do not perceive themselves as getting older, neither that they are old. Other writings on the topic, which resulted in a book chapter, were developed through a literature review concerning the aging of the intellectually disabled. It is suggested, however, that further studies and researches are developed to contribute to the understanding and perception of aging in intellectually disabled